Understanding Disabilities: A Study of Attitudes of Psychology Students toward Disabilities - Hikmiah, Ziadatul; Pratiwi, Ari (The Center for Disability Studies and Services Brawijaya University, 2023)
It is crucial to understand the attitude of psychology students towards disability because psychology students are projected to be engaged in health services, especially mental health. The purpose of this study was to examine the attitudes of psychology students towards disability moderated by gender, class, frequency of contact with disabilities and experiences related to disability. The research method used is correlational quantitative through the distribution of an online self-report scale to 202 psychology students in Indonesia. The results of the analysis show that there is no correlation between attitudes towards persons with disabilities and the frequency of contact with persons with disabilities, especially among students majoring in psychology in Indonesia. The lack of social contact with people with disabilities in the Covid-19 pandemic situation is a major factor as well as opening opportunities for a more thorough study of the attitudes of psychology students towards people with disabilities in this Covid-19 pandemic situation.